Septal augmentation in empty nose syndrome a novel technique: case report - Alfawas Mohamed Abdullah; Ji Yun Choi (Journal of Cosmetic Medicine)
Empty nose syndrome is an uncommon rhinological disease. Nevertheless, it can affect the quality of life of the patient and cause ambiguity in the diagnosis and treatment giving the fact of lacking a specific diagnostic method. We treated a 49-year-old male with a history of multiple nasal traumas and surgeries by performing septal augmentation using a conchal cartilage graft, and he was satisfied with the results. Most common treatment is inferior meatus augmentation. However, septal augmentation and septal deficiency should never be overlooked as it might have the same effect of inferior/middle turbinates deficiency.